Rancang Bangun Sistem Informasi Administrasi Jasa Penitipan Hewan Berbasis Web - Hesti Rian (Universitas Mohammad Husni Thamrin, 2021)
The development of the Animal Care Service Administration Information System is a data input system for Owners, Cats, Types of Packages. Owner data input system includes Owner's Name, Address, and Telephone Number. The cat input system includes Cat Name, Gender, Description, Weight, and Veterinarian Recommendation. The Package Type input system includes Package Type, Price, and Package Description. The purpose of the Veterinary Service Administration system is to facilitate the data management of the Animal Care Service Administration. The development of this system uses the system development life cycle method. The method includes several stages of the process, namely the system planning stage, the system analysis stage, the system design stage, the system implementation stage, the system evaluation stage, the system use and maintenance stage. The Animal Care Service Administration Information System is expected to facilitate the process of making officer reports so that they can produce accurate and effective data.